Proposals for monetary reform: A critical assessment using the general quantity equation by Wolfgang Stützel - Ruben Tarne (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
Europe is still suffering from the turmoil created by the Great Financial Crisis. Finding solutions to the danger of new financial crises is an important criterion for a stable European Union. Proponents of the Sovereign Money System (SMS) identify the ability of private banks to create money as the main contributor to the outbreak of financial crisis. Hence, they want to put the control of the monetary base into the hands of a public institution. This paper will investigate whether the strategy of setting the monetary base - in a SMS - is grounded in realistic assumptions. They claim that the velocity for "real" transactions is stable and therefore, a "workable" link from money base to economic activity can be established. Yet, this claim stands on the shaky assumption that "payment traditions" are unchanging and the dubious concept of "velocity of circulation". Post-Keynesians have criticised the latter, but have not contributed an alternative concept of the relationship between the level of economic activity and the means of payment necessary to achieve it. This, however, would help clarify the critique of a monetary policy strategy, which tries to set the monetary base in the SMS environment, as it would illuminate the specific assumptions that need to hold in order for a link between economic activity and the money supply to be stable. Already in 1957, Stützel tried to establish a relationship - based on balance mechanics - between economic activity and changes in means of payment that was free of the limitations of the equation of exchange. The paper will reformulate Stützel's equation and clarify it with the help of stock-flow consistent Taccounts in order to apply it to the SMS. In doing so, it becomes obvious that the connection between economic activity and changes in means of payment is quite unpredictable. For a stable relationship, a lot of very specific, unrealistic assumptions need to hold. Therefore, the setting of an "optimal" amount of the monetary base in the SMS is, apart from many other of the SMS' problems, not realistic. Stützel's "general quantity equation" provides a clear relationship between money and economic activity that could help the existing endogenous money theory to be more precise in that regard.
Keywords: E41; E42; E51; E58; G01; 330; Sovereign Money; Balance mechanics; Stock-flow consistency; Demand for money; Money supply; Financial crises